Lipoma gástrico: relato de caso - Kim,Daniel Dongiu (2011)
We report a case of gastric lipoma, a rare benign stomach tumor. There are approximately 200 cases previously described in literature. A male, 62-year-old patient with no clinical complaint presented a tumor lesion in the stomach antrum found in a routine upper endoscopy. A surgical resection (subtotal gastrectomy) was done and the histological examination showed submucosal lipoma without signs of malignancy. This report points to the growth of routine examination in the current clinical practice and the dilemma brought by overdiagnosis.